Application of Project-Based Learning Model to Improve Students' Critical Thinking Skills - Ahmad Hamdani; Reza Nuril Fahmi; Suharyanto Soro; Nana Herdiana Abdul Rahman (Civiliza Publishing, Indonesia., 2025)
Low critical thinking skills have a negative impact on the competence of graduate students. Students' low critical thinking skills are caused by one of the learning models that teach critical thinking skills are not used properly in every learning in the classroom. One of the learning models that is in accordance with critical thinking skills is Project Based Learning. The purpose of this study is to determine the level of students' critical thinking skills. The researcher uses a quantitative research paradigm with a quasi-experimental method carried out in the context of secondary education. The research instrument used is Non-equivalent Pretest-Posttest Design. The results of the study show that (1) The application of the Project Based Learning model can improve critical thinking skills; (2) Project-based learning is an effective model approach that focuses on critical thinking in solving problems; (3) The Project Based Learning model can create interaction between students and other students. The conclusion of this study is that the Project Based Learning model is an effective approach in developing students' critical thinking skills.